Increased productivity and sales of the Dapu Rindu home industry - Mayang Murni; Nasrul Kahfi Lubis; Asnidar Asnidar; Agustina Nurul Fajriah (Universitas Muhammadiyah Magelang, 2023)
Home industry is a form of Micro, Small, and Medium Enterprises (MSMEs). Many home industry players manage businesses without having adequate knowledge and skills, one of whom is Dapu Rindu, operating in the food industry, which is experiencing stagnation in all aspects of its business. The aim of this community service is to increase partners' knowledge and skills in managing their businesses, as well as to boost their business productivity and sales. Some of the methods implemented in this program include diversifying products with regional characteristics, improving marketing mix strategies, packaging and branding, and providing financial management training in the form of financial governance, recording, and determining competitive product selling prices. The results of the program show an increase in turnover and business profits, by 18.75% and 25%, respectively. Additionally, it has led to an improvement in partners' skills, enabling them to produce two new products that are typical Acehnese processed foods, possess legal status, calculate competitive selling prices, and manage business finances effectively.